2013
DOI: 10.1589/jpts.25.1575
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Push-ups Plus Sling Exercise on Muscle Activation and Cross-sectional Area of the Multifidus Muscle in Patients with Low Back Pain

Abstract: [Purpose] The purpose of this study was to examine the effect of lumbar stability exercises on chronic low back pain by using sling exercise and push-ups. [Subjects] Thirty adult subjects with chronic back pain participated, with 10 adults being assigned to each of 3 exercise groups: general physical therapy (PT), lumbar stability using sling exercises (Sling Ex), and sling exercise plus push-ups (Sling Ex+PU). Each group trained for 30 minutes 3 times a week for 6 weeks. The Oswestry Disability Index (ODI), s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 18 publications
0
21
0
Order By: Relevance
“…Research results have supported a direct connection between the core stabilizing muscles and the ability to maintain balance [33]. In fact, TRX exercises not only strengthen the body main motional muscles, but also strengthen the core stabilizing muscles by performing a functional activity [34]. It can be concluded that both exercises can have a desirable effect on the static and dynamic balance of athletes.…”
Section: Discussionmentioning
confidence: 79%
“…Research results have supported a direct connection between the core stabilizing muscles and the ability to maintain balance [33]. In fact, TRX exercises not only strengthen the body main motional muscles, but also strengthen the core stabilizing muscles by performing a functional activity [34]. It can be concluded that both exercises can have a desirable effect on the static and dynamic balance of athletes.…”
Section: Discussionmentioning
confidence: 79%
“…SET can promote the coordinated contraction of the trunk, hip, and knee, recruit more muscle groups, and activate local stable muscle groups during the coordinated contraction of the overall muscles, which is helpful to improve the dynamic balance function of the lower limbs[ 33 ]. It can be inferred that the application of SET to ACLR patients can not only effectively activate the strong contraction of the trunk and lower limb muscles and improve the neuromuscular control ability but also promote the strength growth of local muscles around the knee joint[ 36 ], thus enhancing the postural control of ACLR patients.…”
Section: Discussionmentioning
confidence: 99%
“…Twelve weeks of the Neurac sling exercise, a vibration stimulus exercise using a hanging rope, helps to stabilize the lower back and improve posture and balance in the CLBP patient22 ) . Furthermore, six weeks of sling exercises and push-ups were more effective for LSA than sling exercises alone23 ) .…”
Section: Discussionmentioning
confidence: 99%